Teoría de la regulación (en especial, acerca de los fundamentos de la regulación) - Sacristán, Estela Beatriz (2016)
This study analyzes the foundation and the meaning of regulation, specifically from the legal and economic perspective. A basic budget of public interest theories of regulation arises, in a context of freedom. Thus, the role of law as a regulator in society and the various justifications presented for it will be verified.